(untitled) (Global Journal of Human-Social Science, 2014)
Introduction-In all societies, women have claimed equal status with men. It is of a vital importance in modern social science studies, and involves serious research. Progress in attitude, behavior, pattern and legal system is inevitable in all civilized societies. In a progressive society the rights and obligations were determined on the basis of status of an individual. This paper examines historically the status of special reference to Tamil Nadu women. The level of culture of a particular society can very well be judged by the position of women in that society. Women especially the married one, enjoyed a position of respect and authority in the family as well as in society.